2017
DOI: 10.1039/c7ce00608j
|View full text |Cite
|
Sign up to set email alerts
|

Switching of the products by changing the size and shape of catalytic nanoparticles during CVD growth of MoS2nanotubes

Abstract: MoS2 nanotubes are grown by CVD with FeO catalyst nanoparticles, which competes with the formation of SiO2 nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Monolayer MoS 2 was synthesized by an atmospheric pressure CVD (APCVD) with a separate-flow system. The detailed geometry of our APCVD is shown in Figure a. ,, In this system, we can separately control the temperatures of MoO 3 , S, and the substrate as well as the flow rates of the MoO 3 and S lines to guarantee the controllability and reproducibility. MoO 3 (Kanto Chemical Co., Inc., >99.5%) and S (Kanto Chemical Co., Inc., >99.5%) powders were utilized as the source materials without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monolayer MoS 2 was synthesized by an atmospheric pressure CVD (APCVD) with a separate-flow system. The detailed geometry of our APCVD is shown in Figure a. ,, In this system, we can separately control the temperatures of MoO 3 , S, and the substrate as well as the flow rates of the MoO 3 and S lines to guarantee the controllability and reproducibility. MoO 3 (Kanto Chemical Co., Inc., >99.5%) and S (Kanto Chemical Co., Inc., >99.5%) powders were utilized as the source materials without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed geometry of our APCVD is shown in Figure 1a. 7,34,35 In this system, we can separately control the temperatures of MoO 3 , S, and the substrate as well as the flow rates of the MoO 3 and S lines to guarantee the controllability and reproducibility. MoO 3 (Kanto Chemical Co., Inc., >99.5%) and S (Kanto Chemical Co., Inc., >99.5%) powders were utilized as the source materials without further purification.…”
Section: Methodsmentioning
confidence: 99%
“… 12 Thus many researchers have focused on the synthesis of various morphologies of 2H-MoS 2 to improve the number of the active-sites by constructing excessive exposed edges of the layers. MoS 2 nanoflakes, 14,15 nanosheets, 16 nanowires, 17,18 nanotubes, 19 nanoribbons 20 and nanoflowers 21,22 were prepared to increase their active-sites and enhance their photocatalytic performance. Here we have prepared petal-spherical like MoS 2 photocatalysts by hydrothermal method and some of the samples were then sintered at 573 K, 673 K and 773 K for 4 h, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many synthetic methods have been explored to fabricate MoS 2 nanotubes, for example, solvothermal, 9 hydrothermal, 10 high-temperature synthesis, 11 and thermal evaporation methods. 12 Numerous studies have shown that MoS 2 nanotubes have super properties in the application of nanoscale sensors, 13 optoelectronics, 14 electrochemistry, 15 catalysts, 16 and lubrication. 17…”
Section: Introductionmentioning
confidence: 99%